Determinan Karakteristik Ibu Hamil yang Berhubungan dengan Kejadian Preeklampsi - Yuli Farida; Mardianti Mardianti; Ida Farida Handayani; Mira Meida (Journal of Telenursing (JOTING), 2026)
This study aimed to analyze the determinants of maternal characteristics associated with the incidence of preeclampsia. This study used a correlational analysis method with a case-control approach. The results showed that variables simultaneously associated with the incidence of preeclampsia in pregnancy were occupation (P=0.010) and obesity (P=0.011). Obesity was associated with a 3.30-fold increased risk of preeclampsia, while occupation was associated with a 3.10-fold increased risk. Conclusion: Early detection of risk factors, abnormalities, and complications in pregnancy in antenatal care services is crucial, especially when pregnant women work with high physical loads and time patterns, as well as work stress, which are strongly associated with the incidence of preeclampsia. Obesity during pregnancy is also associated with preeclampsia. Therefore, early screening by monitoring body weight (BMI) during pregnancy in antenatal care is crucial for health workers to reduce morbidity and mortality in preeclampsia cases. Keywords: Maternal Characteristics, Pregnancy, Preeclampsia